"Staged Dilemma": Hidden Political Intents in Ghana's Botched Referendum of 2019. Issue 2 (3rd July 2022) - Sabbi, Matthew
Abstract: The cancellation of Ghana's 2019 referendum provoked a public furore after depriving citizens of the promised constitutional right to affect the recruitment of district mayors. The consequent recriminations between the opposition and the incumbent effectively focused on the content of the poll, especially a vicious infiltration of party politics into the municipal councils. Drawing on multiple strands of data and fieldwork experience, this article presents an alternative view that unearths the inherent political equilibrium that undergirded the cancellation of the planned poll. Embedded in the political sociology of referendum, I show that despite their ostensibly competing views on local government, both parties had the end goal of maintaining the status quo, as they implicitly agreed to initiate and terminate the poll. This offered a basis for them to display their varying views on the exercise publicly while cloaking a long-standing convention to safeguard the municipal hierarchy and patronage.